Pengembangan Sistem Informasi Pencatatan Pembayaran SPP Dan Tabungan Berbasis Website - Agus Priyadi; Daniel Rudjiono; Ahmad Zainudin; Siti Sohiroh (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
Advances in technology encourage many agencies to be able to maximize the use of technology. One of the institutions affected is the educational institution. The payment transaction process that is still widely used in educational institutions is a manual transaction. Recording transactions manually raises several problems, one of which is transparency in recording. A web-based information system for paying tuition fees and student savings was developed to maximize the use of existing technology. This research resulted in a system for recording tuition fees and student savings which can be easily used and has good transaction recording transparency. This web-based system was developed using the R&D method. Based on the results of the validation carried out, it shows that the system is good and ready to use.